Problematic smartphone use in college students: the interplay of adverse childhood experiences and lifestyle factors - Yanling Shu; Yunyun Liu; Wenhua Wang; Linfei Dou; Xinghua Yang; Xirennayi Abudurexiti; Lei Zhang; Mingyang Wu; Youjie Wang (Frontiers in Public Health, 2026)
Background The interplay between adverse childhood experiences (ACEs) and lifestyles in influencing problematic smartphone use (PSU) remains unclear. Therefore, we aimed to examine the associations between ACEs and PSU across different lifestyles among college students in China. Methods The participants from six universities were randomly chosen from 57 universities in Shaanxi province in China, using a multistage, random cluster sampling method. ACEs and lifestyles were evaluated using a structured questionnaire and PSU was assessed using the Mobile Phone Addiction Tendency Scale. Binary logistic regression models and additive interaction models were employed to examine the associations between ACEs and PSU across different lifestyles among college students. Results Among the 18,649 college students, 5,538 (29.70%) reported having PSU, and 82.59% of participants had encountered at least one ACE, with 10.69% having experienced four or more ACEs. Among college students with unhealthy lifestyles, students experiencing ≥ 4 ACEs ( OR , 5.82; 95% CI , 4.30–7.92) or any of four ACE categories showed a markedly elevated likelihood of PSU. ACEs and unhealthy lifestyle exerted significant additive effects on the risk of PSU (relative excess risk due to the interaction [ RERI ]: 3.19 for ≥ 4 ACEs, 0.84 for household dysfunction, 1.23 for neglect; attributable proportion due to the interaction [ AP ]: 0.55 for ≥ 4 ACEs, 0.24 for household dysfunction, 0.34 for neglect). Conclusions Our findings suggest that the ACEs and unhealthy lifestyles were associated with elevated likelihood of engaging in PSU among college students. Furthermore, there were positive additive interactions between ACEs and lifestyle factors in relation to PSU.